Atmosphere–soil carbon transfer as a function of soil depth - Balesdent, Jérôme; Basile-Doelsch, Isabelle; Chadoeuf, Joël; Cornu, Sophie; Derrien, Delphine; Fekiacova, Zuzana; Hatté, Christine (Nature (London), 2018)
The exchange of carbon between soil organic carbon (SOC) and the atmosphere affects the climate 1 , 2 and—because of the importance of organic matter to soil fertility—agricultural productivity 3 . The dynamics of topsoil carbon has been relatively well quantified 4 , but half of the soil carbon is located in deeper soil layers (below 30 centimetres) 5 – 7 , and many questions remain regarding the exchange of this deep carbon with the atmosphere 8 . This knowledge gap restricts soil carbon management policies and limits global carbon models 1 , 9 , 10 . Here we quantify the recent incorporation of atmosphere-derived carbon atoms into whole-soil profiles, through a meta-analysis of changes in stable carbon isotope signatures at 112 grassland, forest and cropland sites, across different climatic zones, from 1965 to 2015. We find, in agreement with previous work 5 , 6 , that soil at a depth of 30–100 centimetres beneath the surface (the subsoil) contains on average 47 per cent of the topmost metre’s SOC stocks. However, we show that this subsoil accounts for just 19 per cent of the SOC that has been recently incorporated (within the past 50 years) into the topmost metre. Globally, the median depth of recent carbon incorporation into mineral soil is 10 centimetres. Variations in the relative allocation of carbon to deep soil layers are better explained by the aridity index than by mean annual temperature. Land use for crops reduces the incorporation of carbon into the soil surface layer, but not into deeper layers. Our results suggest that SOC dynamics and its responses to climatic control or land use are strongly dependent on soil depth. We propose that using multilayer soil modules in global carbon models, tested with our data, could help to improve our understanding of soil–atmosphere carbon exchange. This study of whole-soil carbon dynamics finds that, of the atmospheric carbon that is incorporated into the topmost metre of soil over 50 years, just 19 per cent reaches the subsoil, in a manner that depends on land use and aridity.